Bariery kulturowe w słowackim przekładzie Ferdydurke Witolda Gombrowicza - Buczek, Marta (Przekłady Literatur Słowiańskich, 2012)
Cultural barriers in the slovak translation of Witold Gombrowicz’s Ferdydurke The article presents the problem of cultural barriers in Slovak translation of Witold Gombrowicz’s Ferdydurke which was published in a new translation horizon in 2004. The roman was translated by a very well known Slovak translator — Jozef Marušiak. The author of the article shows the translation strategies which were used by him to overcome cultural barriers and reconstruct foreign mental mechanisms as part of different culture. The strategies exploited in the process of reinterpretation of the original meanings were the literal strategy combined with the strategy of neutralization of foreign cultural facts. The question is if it is possible to translate complicated prose of Witold Gombrowicz to Slovak and reinterpret implicated in the original text cultural facts and whether they constitute the cultural barrier in the process of translation. Key words: Witold Gombrowicz, Ferdydurke, translation, polish literature in Slovak translations, cultural barriers in translation.